Mathematical optimization theory and operations research : 19th International Conference, MOTOR 2020, Novosibirsk, Russia, July 6-10, 2020 : revised selected papers /: 19th International Conference, MOTOR 2020, Novosibirsk, Russia, July 6-10, 2020 : revised selected papers. ([2020]) - Unknown
No abstract available